Mutu sebagai Identitas Sekolah: Konsepsi Kualitas dalam Pengelolaan Lembaga Pendidikan - Mu’alimin Mu’alimin; Yuvita Nila Rahayu; Khoirul Anwar (Paedagogos: Journal of Education and Learning, 2026)
The development of education in the era of globalization requires educational institutions not only to function as centers for knowledge transfer but also as institutions capable of ensuring the continuous quality of educational services. Competition among educational institutions encourages schools to build their institutional identity through effective and systematic quality management. Therefore, the study of quality as a school identity is essential to understand how the concept of quality is implemented in educational management. This study aims to analyze the concept of quality in education, identify school quality indicators as reflections of educational quality, and examine the quality of educational administration from the perspective of educational management. This research employed a literature review approach by examining various relevant scientific sources. The data were obtained from the Google Scholar database using the keywords “educational quality,” “school quality,” and “educational quality management” within the period of 2022–2025. The initial search yielded a number of articles that were then selected based on topic relevance and the completeness of scientific information, resulting in five main articles for in-depth analysis. The findings indicate that educational quality is a multidimensional concept encompassing school leadership, teacher competence, organizational culture, and educational evaluation systems. These findings demonstrate that educational quality is not only related to the achievement of academic standards but also to the ability of educational institutions to establish sustainable management systems and strengthen their institutional identity.